Assimilation et intégration dans le refuge huguenot (fin xviie-xviiie siècles) : Nouvelles possibilités, nouvelles méthodologies - Myriam Yardeni (Diasporas: Circulations, Migrations, Histoire)
From the ‘20s of the last century, a series of mini-historiographical revolutions have worked to change our conceptions, methodological approaches and manner of writing history. We can follow these developments through research on emigration, assimilation and integration. In the wake of developments in the field of cultural history, we can now conceptually differentiate between assimilation (a phenomenon of accommodation and acculturation) and integration (a social, political and economic process) – a distinction long maintained in spoken language. These two phenomena took place in parallel but according to totally different rhythms.